O ATENDIMENTO EDUCACIONAL ESPECIALIZADO NA PANDEMIA DE COVID-19 E MEDIDAS COMPENSATÓRIAS DE APRENDIZAGEM PÓS-PANDEMIA: PERSPECTIVA INCLUSIVA - Shirley de Oliveira Ramalho (2024)
The general objective of the research is to understand the educational process of Special Education target students from the perspective of inclusive education during social distancing resulting from the covid-19 pandemic and return to in-person classes. This research aimed to specifically investigate Specialized Educational Assistance in the covid-19 pandemic; the social interaction of the child Target Audience of Special Education in the school process; compensatory learning measures after social distancing from an inclusive perspective, from 2020 to 2022 and official recommendations from the Department of Education on the assessment of school development. The study was developed through qualitative and exploratory research, involving literature review, documentary research and semi-structured interviews. The period during which the research was carried out was from June 2022 to June 2023. The interview followed a script including open questions that deal with the characterization of the participants (professional training and length of experience in teaching); specialized educational assistance during the pandemic period; guidelines and guidance received from the Municipal Department of Education; school intervention for the inclusion process of the target student of Special Education; challenges and successful experiences; compensatory learning measures in the post-pandemic. Two school managers, five teachers specializing in Special Education from an inclusive perspective who worked in the Specialized Educational Service and three parents of students enrolled in the Multifunctional Resource Room participated in the research. Content analysis followed the steps described by Bardin (1977). The results indicated that at the municipal level, social distancing resulting from covid 19 changed the dynamics of the population and brought changes to the process of serving Corumbá students. The need for exceptional changes arose to continue the varied types of service according to the needs and individual pace of the student served, without disregarding the socioeconomic issues involved. Schools organized themselves to face the challenges and created compensatory learning strategies such as: home teaching for Special Education audiences, the “Trilhos do Recomeço para o Avanço Estudantil” project, so as not to leave students unassisted. It is worth highlighting that social inclusion is fundamental, promotes balance, values the diversity and the participation of all individuals in society.